Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Apotek Kabupaten Rembang - Utami, Sally Astya; Cholisoh, Zakky (Universitas Muhammadiyah Surakarta, 2017)
Government regulations regulate pharmaceutical care standards at pharmacies to ensure the quality of pharmaceutical care to patient. The impact of not implementing a good pharmaceutical service activity is that medication errors can occur in the pharmaceutical service process. The study aimed to determine if there is any correlation between customer satisfaction and the application of the standards of pharmaceutical care in Rembang. This is a cross sectional survey research with purposive sampling technique. Data was obtained by distributing questionnaires filled by community pharmacists and patients attending community pharmacies. The study was conducted at 4 (four) community pharmacies in Rembang. Data were analyzed using Pearson correlation. Questionnaires were filled by 4 pharmacists’ measuring aspects of facilities, infrastructure and services. The level of satisfaction of 94 community pharmacies’ patients were measured in 5 dimensions i.e. reliability, assurance, tangibles, empathy and responsiveness. The quality of pharmaceutical care scoring and patients’ satisfaction showed no relationship p (95%; 2 tailed) = 0.503.